SOCIAL-PSYCHOLOGICAL FACTORS OF ADOLESCENTS’ SOCIALIZATION IN A CRISIS ENVIRONMENT - Хоменко-Семенова, Леся; Рожківський, Андрій; Павленко, Олександр (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article provides a theoretical analysis and empirical study of the socio-psychological factors of adolescent socialization in a crisis environment The purpose of the article is to theoretically define and empirically study the socio-psychological factors of adolescent socialization in a crisis environment; Results. In the course of the empirical study, we used the following methods: the author’s questionnaire aimed at studying the social factors of the formation of socialization in adolescents in modern society; the questionnaire "Your Life Optimism" (V. A. Semichenko); the multilevel personality questionnaire "Adaptability" (A. G. Maklakova and S. V. Chermyanina); the Guilford test "Social Intelligence". The study found that the socio-psychological factors of socialization of adolescents are: The family is one of the social institutions, the psychological essence of which is considered in many studies. The education system, namely the school environment, stands out as the second (along with the family) leading institution of socialization. The peer group plays a key role in shaping the socialization of individuals, which is the object of study of both sociology and psychology. Mass media (media), such as television, radio, the Internet, newspapers and magazines, play a significant role in the socialization process, contributing to the transmission of cultural values, standards of behavior and norms of society. The coronavirus (COVID-19) pandemic has been marked by dramatic changes in all aspects of society, including socialization. War plays a critical role in the socialization of adolescents, affecting all aspects of their lives, from social skills to emotional state. Conclusion. The empirical study showed the following results: using the multilevel personality questionnaire "Adaptivity" (A. G. Maklakov, S. V. Chermyanina) it was found that 37% of respondents belong to the group of satisfactory adaptation. They are able to adapt to changes, although this process requires more time and effort; 62.8% of respondents have a high or normal level of adaptation, which indicates their ease of adaptation to new conditions and changing circumstances. Using the Guilford test "Social Intelligence" it was found that: 44.2% of respondents have an average level of social intelligence, 37.2% of respondents demonstrated a level of social intelligence above average, which indicates their high ability to effectively interact in society. Diagnostics of the level of life optimism using the questionnaire “Your Life Optimism” (V. A. Semichenko) showed that in 39.5% of respondents the level of optimism decreased from high to medium, which is associated with significant emotional changes and the impact of negative events, such as war; 46.5% of respondents maintained a stable level of optimism, demonstrating emotional stability. Using the author’s questionnaire, the main social factors that contribute to the adaptation of adolescents to the crisis environment were identified, in particular, the influence of family, peers, educational institutions and the media. The results demonstrate the complex impact of the modern crisis environment on the socialization of adolescents, as well as the variability of their adaptability and emotional stability.